The Ottoman press, 1908-1923 - Baykal, Erol A. F. (The Ottoman Empire and its Heritage, 2019)
The Ottoman Press (1908-1923) looks at Ottoman periodicals in the period after the Second Constitutional Revolution (1908) and the formation of the Turkish Republic (1923). It analyses the increased activity in the press following the revolution, legislation that was put in place to control the press, the financial aspects of running a publication, preventive censorship and the impact that the press could have on readers. There is also a chapter on the emergence and growth of the Ottoman press from 1831 until 1908, which helps readers to contextualize the post-revolution press.